A novel alpha kinase EhAK1 phosphorylates actin and regulates phagocytosis in Entamoeba histolytica. - M Shahid Mansuri (Public Library of Science (PLoS), 2014)
Phagocytosis plays a key role in nutrient uptake and virulence of the protist parasite Entamoeba histolytica. Phagosomes have been characterized by proteomics, and their maturation in the cells has been studied. However, there is so far not much understanding about initiation of phagocytosis and formation of phagosomes at the molecular level. Our group has been studying initiation of phagocytosis and formation of phagosomes in E. histolytica, and have described some of the molecules that play key roles in the process. Here we show the involvement of EhAK1, an alpha kinase and a SH3 domain containing protein in the pathway that leads to formation of phagosomes using red blood cell as ligand particle. A number of approaches, such as proteomics, biochemical, confocal imaging using specific antibodies or GFP tagged molecules, expression down regulation by antisense RNA, over expression of wild type and mutant proteins, were used to understand the role of EhAK1 in phagocytosis. EhAK1 was found in the phagocytic cups during the progression of cups, until closure of phagosomes, but not in the phagosomes themselves. It is recruited to the phagosomes through interaction with the calcium binding protein EhCaBP1. A reduction in phagocytosis was observed when EhAK1 was down regulated by antisense RNA, or by over expression of the kinase dead mutant. G-actin was identified as one of the major substrates of EhAK1. Phosphorylated actin preferentially accumulated at the phagocytic cups and over expression of a phosphorylation defective actin led to defects in phagocytosis. In conclusion, we describe an important component of the pathway that is initiated on attachment of red blood cells to E. histolytica cells. The main function of EhAK1 is to couple signalling events initiated after accumulation of EhC2PK to actin dynamics.